Increasing Awareness of the Younger Generation on Political Participation in General Elections - Hasugian, Marudut; Firman; Sofian , Muhamad (PT. Anagata Sembagi Education, 2025)
General elections are the main pillars of Indonesian democracy as stipulated in Article 27 of the 1945 Constitution of the Republic of Indonesia and Law Number 7 of 2017 concerning General Elections. The younger generation, which makes up about 55% of the total electorate, has a strategic role in determining the political direction of the nation. However, the phenomenon of political apathy and white groups (golput) among the younger generation shows a low awareness of their constitutional rights and obligations. This research aims to analyze efforts to increase the political awareness of the younger generation through political education and legal socialization. The method used is counseling and mentoring activities for students of SMK Negeri 8 Information and Communication Technology Jayapura on July 25, 2025. The results of the study show that systematic and comprehensive political education is able to increase the understanding of the younger generation about the importance of participation in elections, the right to vote as citizens, as well as the dangers of politicization and irrational mobilization. In conclusion, increasing the political awareness of the younger generation requires synergy between election organizers, the government, and educational institutions to form rational, critical, and actively participating voters in the democratic process.